A comparative study on flocculating ability and growth potential of two microalgae in simulated secondary effluent. (April 2016) - Lv, Junping; Guo, Junyan; Feng, Jia; Liu, Qi; Xie, Shulian
Highlights: The self-flocculating property of Chlorococcum sp. GD was firstly reported. Chlorococcum sp. GD had excellent flocculating ability. The excellent flocculating ability of Chlorococcum sp. GD was related to EPS. Pollutants in secondary effluent were effectively removed by Chlorococcum sp. GD. The lipid content of Chlorococcum sp. GD was high. Abstract: The flocculating ability was an important property to microalgal harvesting, especially in secondary effluent. In this study, the flocculating ability of two microalgae, Chlorococcum sp. GD and Parachlorella kessleri TY, was evaluated after 10 d of cultivation in secondary effluent. After 180 min of settling, the flocculating ability of Chlorococcum sp. GD and P. kessleri TY was 84.43% and 16.23%, respectively. It was suggested that Chlorococcum sp. GD was an excellent self-flocculating microalgae. The mechanism on self-flocculating of Chlorococcum sp. GD was probably related to hydrophobic extracellular polymeric substances (EPS). Besides, compared to P . kessleri TY, the nitrogen and phosphorus removal efficiency of Chlorococcum sp. GD was high, which was up to 66.51% and 74.19%, respectively. Chlorococcum sp. GD also had high lipid content and biomass concentration. Therefore, Chlorococcum sp. GD could be regarded as a promising candidate for microalgal cultivation and harvesting in secondary effluent.